Entre autorité fédérale et provinciale : territoire et ressources dans les provinces de l’ouest canadien - Marine Le Puloch (Centre de Recherches sur les Mondes Américains, 2008)
In western Canada, aboriginal rights to land and its underground resources are intimately linked to the terms of the so-called numbered treaties signed, between 1871 and 1921, between First Nations and the federal government. Even though the central government had not yet obtained from the entire aboriginal population an agreement to adhere to the treaties already signed, it transferred Crown land to the western provinces in 1930. It was therefore agreed that the provinces would transfer back land to the federal government for the establishment of reserves for the exclusive use of the aboriginal nations which would adhere to treaties. Thus, the western provinces became part of the negotiations of adhesions to the numbered treaties even though the federal government, guardian of the aboriginal population, held, and still holds, exclusive authority over aboriginal affairs. As a result, and in spite of the guardian status of the central government, laws, whether provincial or federal, are often contrary to the interests of American Indians and they generate a number of conflicts.